1998
DOI: 10.1046/j.1365-2141.1998.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 13 and myeloid malignancy — characteristic blast cell morphology: a United Kingdom Cancer Cytogenetics Group survey

Abstract: Summary.We retrospectively report data on 28 patients with haematological malignancy and trisomy 13 (25 cases) or tetrasomy 13 (three cases) as the primary acquired cytogenetic change. Peripheral blood and/or bone marrow morphology was reviewed in 25/28 cases and the final diagnosis was as follows: AML M0 (11), AML M1 (6), AML M2 (2), AML M4 (2), AML M5b (1), AML M6 (1), RAEB-t (3), RAEB (1), RA (1). All three cases with tetrasomy 13 had AML M0. Characteristic small hand-mirror blasts with cytoplasmic blebs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Of the 52 patients, material from 8 patients showed extra copies of chromosome 13 (15 %, Table 1), a high percentage which agrees with published reports. 4,6,7 Seven out of the 8 patients with trisomy 13 (87.5%) showed mutations in RUNX1 (Table 1), while 7 out of the 16 patients with RUNX1 mutations (44%) had trisomy 13. Statistical analysis (one-sided Fisher's exact test) showed that trisomy 13 and RUNX1 mutation co-occurred more frequently than expected by chance (p<0.00056).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 52 patients, material from 8 patients showed extra copies of chromosome 13 (15 %, Table 1), a high percentage which agrees with published reports. 4,6,7 Seven out of the 8 patients with trisomy 13 (87.5%) showed mutations in RUNX1 (Table 1), while 7 out of the 16 patients with RUNX1 mutations (44%) had trisomy 13. Statistical analysis (one-sided Fisher's exact test) showed that trisomy 13 and RUNX1 mutation co-occurred more frequently than expected by chance (p<0.00056).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown an association between trisomy 13 and morphologic and immunophenotypic undifferentiated leukemia, in particular within the rare FAB subgroup AML-M0. [1][2][3][4][5][6][7] The majority of cases with trisomy 13 show low remission rates. 2,3,6,8 The biological consequence of an additional copy of chromosome 13 in AML is unknown and has not yet been addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Per Mehta et al (1998), median patient survival was 3 months. The paper by Dohner et al described 8 individuals with trisomy 13 as the sole cytogenetic abnormality, with survival ranging from 0.5 to 14.7 months.…”
Section: Prognosismentioning
confidence: 99%
“…According to Mehta et al (1998), characteristic small hand-mirror blasts with cytoplasmic blebs and tails and scanty small granules were seen in 13/24 cases and 18/25 cases had small blasts would could easily be mistaken for lymphoblasts. Morphologic findings in bone marrow, according to Mesa et al were: median of 80% cellularity, 21% median bone marrow blasts (range 1%-94%), myelodysplastic changes in 56%, reticulin fibrosis in 11%, and ringed sideroblasts in 11% of cases.…”
Section: Pathologymentioning
confidence: 99%